Rent Imputation for Welfare Measurement : A Review of Methodologies and Empirical Findings - Balcazar, Carlos Felipe; Ceriani, Lidia; Olivieri, Sergio; Ranzani, Marco (World Bank Group, Washington, DC, 2014)
As well acknowledged in the literature, housing is often the dominant consumption good for most households. As such, it should be included in a comprehensive welfare aggregate to measure people's living standards accurately. However, assigning a value to the flow of the dwelling for homeowners and nonmarket tenants is problematic. Over the last decades several estimation techniques have been proposed and implemented by practitioners covering from very simple to sophisticated approaches. This paper provides an extensive review of different methods to impute rent, commonly used for welfare analysis. It also gives an overview of how this problem has been addressed by other economic domains, namely national accounts, price indices, purchasing power parities, and taxation. Finally, after setting up a theoretical framework, the paper summarizes the empirical findings about the distributional impact of including imputed rents in welfare aggregates.